Genetic and epidemic characteristics of porcine parvovirus 7 in the Fujian and Guangdong regions of southern China - Zhang, Xinjie; Zheng, Canyang; Lv, Zixin; Xue, Shaohua; Chen, Yuxuan; Liu, Yanru; Huang, Xirong; Luo, Guoqing; Yang, Xiaoyan; Dai, Ailing (Frontiers in Veterinary Science, 2022)
Porcine parvovirus (PPV) is the primary cause of reproductive disorders in pigs. The porcine parvovirus 7 (PPV7) subtype was first identified in the United States in 2016. In this study, PPV7 was detected in different porcine samples, including serum, feces, saliva, and milk, from 69 pig farms in the Fujian and Guangdong regions of South China, and its coinfection with porcine circovirus 2 (PCV2), porcine circovirus 3 (PCV3), and porcine reproductive and respiratory syndrome virus (PRRSV) was determined. Whole-genome sequencing, phylogenetic analysis, and recombination analysis were performed on seven isolates, with each selected isolate originating from a different farm. There was a high rate of PPV7 positivity in blood, stool, and saliva but PPV7 DNA was absent from breast milk. The findings also showed that PPV7-positive samples had a high rate of coinfection with PCV2, PCV3, and PRRSV. Real-time PCR was used to determine the viral copy numbers of PCV2, PCV3, PRRSV, and PPV7 in serum samples and to assess whether PPV7 affected PCV2, PCV3, and PRRSV viral loads. Phylogenetic analysis showed that PPV7e and PPV7f were the most prevalent and widespread subtypes in the Fujian and Guangdong regions, respectively. While the PPV7a, PPV7b, PPV7c, and PPV7f subtypes were most prevalent in Fujian Province, PPV7a-e subtypes were prevalent in Guangdong, indicating that PPV7 has rich genetic diversity in these regions. A putative recombinant strain, 21FJ09, was identified using SimPlot and the Recombination Detection Program 4 software.